ECOLOGICAL STUDY OF THE SUNDA PANGOLIN (MANIS JAVANICA DESMAREST, 1822) IN THE NATURE TOURISM PARK OF BUKIT TANGKILING, CENTRAL KALIMANTAN, INDONESIA - Lorensi, Monika; Gunawan, Yohanes Edy; Rizki, Muhammad (BIOMA : Jurnal Ilmiah Biologi, 2024)
The Sunda pangolin, also known as Manis javanica, is a vulnerable mammal that can be found in Java, Sumatra, and Kalimantan. Unfortunately, due to hunting, poaching, land changes, and forest fires, particularly in Kalimantan, this species is now categorized as endangered on the IUCN Red List. To support conservation efforts and sustainability of the Sunda pangolin, it is crucial to gather more evidence about its ecological study and habitat. Therefore, this study aimed to determine the characteristics of the habitat and distribution of the Sunda pangolin in the Bukit Tangkiling Nature Park, Central Kalimantan. We surveyed between February and June 2022 using a Visual Encounter Survey (VES) combined with burrow count methods and camera traps. The survey included vegetation, potential nest and prey, and abiotic factors for the Sunda pangolin. We found a total of two individuals using a camera trap in plot 1 and direct observation in plot 3. Additionally, we located five potential Sunda pangolin nests. According to the distribution map, the Sunda pangolin can be found in hilly and valley areas, with an estimated population of 7.14 individuals/Ha. Vegetation analysis revealed an importance value index (IVI) of 148.84% for Acacia mangium. Based on PCA results, the abiotic factors of air and soil humidity support the existence of the Sunda pangolin and its nests. We also identified eight species of Hymenoptera and one species of Isoptera, which are potential food sources for the Sunda pangolin. Overall, this study provides essential information to support conservation efforts and sustainability of the Sunda pangolin in Kalimantan.